HUMAN RESOURCES DEVELOPMENT BASED ON COMPETENCE - Jihad, M. Zahrul (Entrepreneur, 2011)
AbstractThis paper tries to give framework for human resource management at various organizational forms that we will encounter in the future. The significance of human resource management in the coming decades encourages us to find a solution that has proven its effectiveness rather than experimenting with ideas that have not been clear and tested.Management that competency-based human resources can help meet the requirements of 3 of 4 is convinced that the organization has a manager who can show the right leadership, employees know what to do for all the information accepted and competencies needed for success.Keywords: Competency, Human ResourcesAbstrakTulisan ini mencoba memberikan kerangka untuk manajemen sumber daya manusia pada berbagai bentuk organisasi yang akan kita hadapi di masa depan. Arti penting dari manajemen sumber daya manusia dalam dekade mendatang mendorong kita untuk menemukan solusi yang telah terbukti efektifitasnya ketimbang bereksperimen dengan ide-ide yang belum jelas dan tested.Management yang berbasis kompetensi sumber daya manusia dapat membantu memenuhi persyaratan 3 dari 4 adalah yakin bahwa organisasi memiliki manajer yang dapat menunjukkan kepemimpinan yang tepat, karyawan tahu apa yang harus dilakukan untuk semua informasi diterima dan kompetensi yang dibutuhkan untuk sukses.Kata kunci: Kompetensi, Sumber Daya Manusia